Review of revenue accounting implementation at PDAM XYZ based on SAK EP - Nural Achmad Raainaa (Akuntansiku, 2026)
This study aims to: 1) determine the application of revenue accounting at PDAM XYZ, and 2) determine the suitability of the application of revenue accounting at PDAM XYZ with SAK EP. This research is a qualitative research with a descriptive approach. Data were collected through literature, interviews, observation and documentation. Then analyzed qualitatively. The research findings reveal: 1) In recognizing water revenue, the company uses the accrual method. The use of this method is appropriate and relevant, because the activity or transaction of selling water to customers cannot directly generate cash receipts. The company must first fulfill its obligations in the form of providing clean water to customers, then recognize revenue by issuing water billing which serves as proof of the right to collect against customer obligations after the goods and/or services have been provided by the company. At the end of each water usage period, customer relations officers will visit the customer's home and record the numbers on the water meter, this aims to determine the volume of clean water usage by each customer. The company will process the water usage data to determine the amount of revenue the company will receive. Next, the company issues a water bill in the form of a Billed Account List (DRD) which will become the customer's obligation and must be paid within the time period determined by the company. 2) The revenue measurement applied by PDAM XYZ is in accordance with SAK EP, namely based on the fair value of payments received or accrued. Revenue is received by the company in cash. The value of water revenue is determined by multiplying the volume of customer water usage during a period by the drinking water tariff in accordance with Mayoral Regulation No. 55 of 2005. Non-water revenue is assessed based on a decision of the board of directors (internal company), so the company can determine the appropriate amount of fees charged to customers for each transaction. These costs charged to customers are measured based on the fair value of the equipment and services required for the transaction. Non-operating income, such as deposit interest and bank interest (giro fees), is calculated by the company by multiplying the bank interest rate by the amount of money the company holds in the bank. For non-operating income other than deposit interest and bank interest, the amount of revenue is measured based on the fair value related to the gross economic benefits received.